Professional Azure SQL Database Administration : Equip yourself with the skills you need to manage and maintain your SQL databases on the Microsoft cloud /: Equip yourself with the skills you need to manage and maintain your SQL databases on the Microsoft cloud. (2018) - Osama, Ahmad
No abstract available